Role of Dinacharya in Prevention of COVID-19 (International Journal of Ayurveda and Pharma Research, 2022)
World is facing an unprecedented pandemic of covid-19 caused by SARS-CoV-2. Globally about 340,543,962 were suffered and 5,570,163 deaths were recorded. This covid-19 is affecting physical as well as psychological levels. Ayurveda is science of life which deals with physical and mental well-being. The awareness about oneself, maintenance of health and boosting up immunity is achieved by Ayurveda. Ayurveda has come forward in this critical situation. Preventive measures are more important in such infectious diseases. Boosting the body’s natural immunity plays a significant role in maintenance of health. Ayurveda has explained about Dinacharya (daily regimen), Ritucharya (seasonal regimen), pursuing these regimen can lead to prevention of such types of infectious diseases. Principle of Dinacharya is connected with body and environment, this will balance the Doshas and keep biological clock regular. It can be extremely effective in restoring health as well as in prevention. Importance of Uthapana, Dantadhavna, Jivhanirlekhniya, Gandusha, Abhyanga, Vyayama for the restoration of health in this pandemic era is reviewed. This is basically an ideal lifestyle in form of daily regimen. In busy life, everyone need to understand the importance of Dinacharya (daily regimen). One should follow Dinacharya (daily regimen) and boost their Bala (strength) to fight against virus, bacteria.